Percutaneous Closure of Patent Foramen Ovale in the Setting of Pulmonary Embolism (Right-Left Shunt Causing Severe Hypoxia). Issue 5 (September 2020) - Johnson, Joel; Kodra, Arber; Basman, Craig; Scheinerman, S. Jacob; Patel, Nirav; Kliger, Chad
A patent foramen ovale (PFO) is well known to cause paradoxical embolism and stroke, but a less appreciated and life-threatening complication can occur when combined with severe pulmonary embolism (PE). Acutely elevated right-sided pressures from right ventricular strain due to PE can lead to right-to-left (R-L) shunting through the PFO and exacerbate hypoxia. We report a case of a 50-year-old female patient with massive PE with further desaturation from R-L shunting from a PFO that benefitted from percutaneous closure of the interartrial communication. Our patient recovered without any complications and had excellent long-term follow-up.